Role of transvaginal ultrasonographic cervical assessment in predicting the outcome of induction of labor - Aggarwal, Kiran; Yadav, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Induction of labor is the most common intervention in modern obstetrics. The pre-induction ‘favourability’ of the cervix as assessed by the bishop score is very subjective. Transvaginal sonography appears to be a feasible alternative to the traditional bishop’s score. Aim of this study, was to compare cervical assessment by transvaginal sonography and digital examination in prediction of outcome of labor induction. Methods: Three hundred women at term with maternal and foetal indications for labor induction were included in the study. Modified Bishop score was assessed by digital examination and the cervical length was measured by Transvaginal sonography (TVS). Successful labor induction was taken as a vaginal delivery within 24 hours from the start of induction. Data were analyzed using SPSS for Windows 15.0. Results: Labour induction was successful in 81.33% of patients. Mean cervical length by digital examination was 2.6 cm, whereas the mean sonographic cervical length was 3.4cm. There was a significant difference of 0.8cm in mean cervical length measured by two methods (P=0.01). The best cut off point for predicting successful induction of labor was ≤3.4cm for sonographic cervical length (sensitivity 0.82, specificity 0.87, positive predictive value 0.77 and negative predictive value 0.25). The best cut off point for Modified Bishop score was 2 (sensitivity 0.95, specificity 0.93). The ROC curve showed that compared to TVS cervical length, Modified Bishop score was the best parameter for predicting successful induction of labor. Conclusions: Transvaginal sonographic cervical length measurement can be used as an adjunct tool to the traditional Bishop score for predicting successful labor induction in high risk pregnancies.